Experience of using Odessa region limestones as foundation base - Mitinskiy, Vasiliy; Novskiy, Oleksandr; Novskiy, Vasiliy (Academic journal Industrial Machine Building Civil Engineering, 2018)
The characteristic properties of limestone-shell rock used as foundation base, including shear resistance transformation into friction resistance, are described. The main provisions of the method for determining piles bearing capacity using limestone mechanical characteristics dependence on the tensile strength under uniaxial compression in Odessa region. The results of limestone-shell rock full-scale tests by bored piles are presented. Experimental values of piles bearing capacity are compared with the values obtained by calculation using different methods.